Patient-Centered Outcomes in Critical Illness: Will My Patient Be Functionally and Cognitively Intact? - Geer, Jacqueline H.; Qi, Wei; Ferrante, Lauren E. (Seminars in Respiratory and Critical Care Medicine, 2019)
Survival in the intensive care unit (ICU) has steadily increased over the past several decades; millions of patients now survive a critical illness every year. ICU survivors are at a significantly increased risk of impairments in physical function, cognitive function, and mental health. These patient-centered outcomes are among the most meaningful to patients. Landmark studies concerning treatment preferences have demonstrated that patients value functional and cognitive outcomes over mortality. In this chapter, we discuss the determinants of functional and cognitive outcomes post critical illness to address the question, “Will my ICU patient be functionally and cognitively intact?”
Keywords: critical illness; cognitive impairment; long-term outcomes; ICU; neuromuscular weakness; critical illness myopathy; quality of life